PERLINDUNGAN HUKUM TERHADAP PRIVASI INFORMASI DATA PRIBADI KONSUMEN JASA LAYANAN TRANSPORTASI ONLINE - Fitriyani, Fitriyani; Amini, Fitria (Law Journal (LAJOUR), 2025)
The development of information technology in the digital era has given birth to various application-based services, including online transportation such as Gojek and Grab. These services offer various conveniences for consumers, such as easy access, affordable rates, and 24-hour service. However, behind these conveniences, there are serious problems related to the protection of users' personal data. This study aims to examine the legal protection of the privacy of personal data of consumers of online transportation services in Indonesia. The research method used is normative with a legislative approach. Data were obtained through literature studies covering primary, secondary, and tertiary legal materials. The results of the analysis show that although there are regulations such as the ITE Law and other regulations, protection of consumers' personal data is still weak. This is evidenced by the rampant misuse of data by third parties without user consent. Collective awareness is needed, both from the government, business actors, and the community, to strengthen legal protection of personal data, as well as the formation of special regulations that regulate data protection as a whole.